Introduction to forensic social work - Natale, Anthony P. (Handbook of forensic social work, 2024)
The first chapter of this text begins with a brief orientation to the history of the current criminal justice system in the United States and forensic social work. The criminal justice system in the United States is both complicated and nuanced. Therefore, a foundation of knowledge associated with the development of this system clarifies the current state of both legal systems and practice. Next, forensic social work is detailed, including how it’s defined, followed by an examination of current challenges in forensic social work. The chapter concludes with a discussion of the organization of the text and recommendations on how to maximize its utility.